2006
DOI: 10.1017/s1461145706007061
|View full text |Cite
|
Sign up to set email alerts
|

Calpain- and caspase-mediated αII-spectrin and tau proteolysis in rat cerebrocortical neuronal cultures after ecstasy or methamphetamine exposure

Abstract: Abuse of 3,4-methylenedioxymethamphetamine (MDMA or Ecstasy) and methamphetamine (Meth or Speed) is a growing international problem with an estimated 250 million users of psychoactive drugs worldwide. It is important to demonstrate and understand the mechanism of neurotoxicity so potential prevention and treatment therapies can be designed. In this study rat primary cerebrocortical neuron cultures were challenged with MDMA and Meth (1 or 2 mM) for 24 and 48 h and compared to the excitotoxin N-methyl-D-aspartat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 39 publications
4
44
0
Order By: Relevance
“…Our results show that retinal neural cells exposed to MDMA also die by a caspase-dependent apoptotic pathway, which are in agreement with in vivo and in vitro studies reporting that MDMA stimulates apoptotic cell death by activating caspase-3 in rat cortical neurons (Stumm et al, 1999;Meyer et al, 2004;Capela et al, 2006Capela et al, , 2007CunhaOliveira et al, 2006), PC12 cells (Milhazes et al, 2006), rat primary cerebrocortical neurons (Warren et al, 2006), human serotonergic cells (Simantov and Tauber, 1997) and in rat limbic system (Tamburini et al, 2006). In order to dissect the mechanism of the neuroprotection induced by NPY, we investigated the protective effect of this peptide on apoptotic cell death caused by MDMA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results show that retinal neural cells exposed to MDMA also die by a caspase-dependent apoptotic pathway, which are in agreement with in vivo and in vitro studies reporting that MDMA stimulates apoptotic cell death by activating caspase-3 in rat cortical neurons (Stumm et al, 1999;Meyer et al, 2004;Capela et al, 2006Capela et al, , 2007CunhaOliveira et al, 2006), PC12 cells (Milhazes et al, 2006), rat primary cerebrocortical neurons (Warren et al, 2006), human serotonergic cells (Simantov and Tauber, 1997) and in rat limbic system (Tamburini et al, 2006). In order to dissect the mechanism of the neuroprotection induced by NPY, we investigated the protective effect of this peptide on apoptotic cell death caused by MDMA.…”
Section: Discussionsupporting
confidence: 92%
“…The neurotoxicity induced by MDMA was also demonstrated in cultured rat cortical neurons (Capela et al, 2006;Warren et al, 2006), liver cells (Montiel-Duarte et al, 2002), cerebella granule cells (Jimenez et al, 2004), and PC12 cells (Milhazes et al, 2006). Although some studies showed that considerable amounts of MDMA can reach the vitreous humor and the eye globe De Letter et al, 2000, the toxic effect of MDMA on the retina is not completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Rat primary cultured prefrontal cortex and striatal neurons were exposed to 0.2 mM, 0.4 mM, 0.6 mM, 0.8 mM and 1.0 mM METH for 24 h. These concentrations were selected based on the LC25 (0.58 mM) of METH in rat primary culture neurons measured in our lab and also based on the concentrations used in other studies (Warren et al, 2007; Chou et al, 2008). These concentrations are similar to the concentrations used in PC12 cell experiments.…”
Section: Resultsmentioning
confidence: 99%
“…When the MAP kinase kinase (MEK1/2) inhibitor U0126 (Calbiochem, EMD Chemicals Inc. San Diego, CA) was used, cells were pretreated for 1 hr with 10 µM U0126 or its vehicle before and during the time of 6-OHDA exposure. Because very little toxicity was seen 6 hr post-METH treatments (data not shown) we chose to use the 24 hr time point, which is the most common time point used for in vitro studies looking at the effect of METH on cell viability [35], [36], [37], [38], [39].…”
Section: Methodsmentioning
confidence: 99%